Diversity and evolution of plant diacylglycerol acyltransferase (DGATs) unveiled by phylogenetic, gene structure and expression analyses - Andreia Carina Turchetto-Zolet (Genetics and Molecular Biology)
Abstract Since the first diacylglycerol acyltransferase (DGAT) gene was characterized in plants, a number of studies have focused on understanding the role of DGAT activity in plant triacylglycerol (TAG) biosynthesis. DGAT enzyme is essential in controlling TAGs synthesis and is encoded by different genes. DGAT1 and DGAT2 are the two major types of DGATs and have been well characterized in many plants. On the other hand, the DGAT3 and WS/DGAT have received less attention. In this study, we present the first general view of the presence of putative DGAT3 and WS/DGAT in several plant species and report on the diversity and evolution of these genes and its relationships with the two main DGAT genes (DGAT1 and DGAT2). According to our analyses DGAT1, DGAT2, DGAT3 and WS/DGAT are very divergent genes and may have distinct origin in plants. They also present divergent expression patterns in different organs and tissues. The maintenance of several types of genes encoding DGAT enzymes in plants demonstrates the importance of DGAT activity for TAG biosynthesis. Evolutionary history studies of DGATs coupled with their expression patterns help us to decipher their functional role in plants, helping to drive future biotechnological studies.